Taguchi and BEM Analyses on the Productivity Performance of an Oil Reservoir - M. N., Mohamad Ibrahim; S., Shuib (2005)
The application of Taguchi Robust Design Technique (TRDT) coupled with the Boundary Element Menthod (BEM) in analyzing the productivity performance of an oil reservoir is presented in this paper. Several reservoir rock and reservoir fluid properties; i.e. permeability, thickness, porosity and viscosity, were choosen in this study. The BEM allows the overall simulation of reservoir performance to be made; whereas the used of TRDT allows us to rank the most influencing factor (property) that affects the productivity performance of the reservoir. Numerical values obtained from the BEM analysis will be used as input data for the TRDT statistical analysis. Result indicated that oil viscosity is the most important factor that affects the productivity performance of the oil reservoir followed by the thickness of the pay zone, the rock permeability and the rock porosity. Results of this study can be used by reservoir engineer in making the right choice of Enhance Oil Recovery techniques that is the most suitable for the reservoir.